2019
DOI: 10.1101/860197
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Species, causes, and outcomes of wildlife rehabilitation in New York State

Abstract: 24 Wildlife rehabilitation is a publicly popular though highly controversial practice. State wildlife 25 agencies frequently debate the ecological impact of rehabilitation. Analysis of case records could 26 inform that debate by clarifying and quantifying the causes for rehabilitation, species involved, 27 and treatment outcomes. This information could aid in the ability of regulatory agencies and 28 rehabilitators to make informed decisions and gain insight into causes of species decline. In New 29 York, reha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Admissions due to anthropogenic causes had a higher mortality rate (57%) than natural causes (40%), and our more refined analysis suggested that infection/parasite admissions were associated with the highest mortality rates (90%), whereas orphaned birds were associated with the lowest mortality rate (16%). Raptors admitted due to being orphaned tend to have higher survival probabilities than those admitted for other reasons, as evidenced by existing studies (Hanson et al, 2021;Lukesova et al, 2021 [see "Nestlings" and "Incubation" in Table 3]).…”
Section: Predominate Causes Of Admission To Wrc May Vary By Countrymentioning
confidence: 82%
See 2 more Smart Citations
“…Admissions due to anthropogenic causes had a higher mortality rate (57%) than natural causes (40%), and our more refined analysis suggested that infection/parasite admissions were associated with the highest mortality rates (90%), whereas orphaned birds were associated with the lowest mortality rate (16%). Raptors admitted due to being orphaned tend to have higher survival probabilities than those admitted for other reasons, as evidenced by existing studies (Hanson et al, 2021;Lukesova et al, 2021 [see "Nestlings" and "Incubation" in Table 3]).…”
Section: Predominate Causes Of Admission To Wrc May Vary By Countrymentioning
confidence: 82%
“…For example, Molina‐López et al (2011) found that trauma accounted for 50% of raptor admissions to a WRC in Spain, with the cause of injury unascertainable for more than half of these. Trauma admissions were also most numerous (56%) in a study of 3212 raptor admissions to a WRC in New York State, USA (Hanson et al, 2021). In South Africa, an analysis of eight years of admissions data for 39 raptor species revealed that vehicle and building collisions were the most common cause of admission (Thompson et al, 2013), and another South African study found that 52% of all admissions for 33 raptor species were also due to collision‐related injuries (Maphalala et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant differences recorded amongst different species' release rates can be attributed to the intrinsic characteristics of the species (animals more resistant or more adaptable to captivity than others) and to the types of debilitation suffered by the different species (e.g. infections, wounds, traumas, fractures) (Molina-López et al 2017;Hanson et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The number of European hedgehogs admitted to rescue centers has been increasing over the last ten years [ 11 ] and a similar trend can also be seen in many other animal species [ 24 27 ]. Various studies have also found an extremely high rate of admission of young animals to rescue centers [ 28 , 29 ]. This fact may be explained in several ways.…”
Section: Discussionmentioning
confidence: 99%